Analysis of the Characteristics of Dominant Diseases in Traditional Chinese Medicine: Based on 95 Diseases. (6th June 2022) - Wu, Hanting; Liang, Yi; Li, Qiushuang; Hei, Peijie; Liang, Juan; Dai, Rongchen; Ji, Conghua
Abstract : Background . Traditional Chinese medicine (TCM) has been widely used all over the world and has shown its superiority in some diseases. However, there are no clear evaluation criteria for TCM. In 2019, a list of TCM dominant diseases was published by the Chinese National Administration of Traditional Chinese Medicine. This study aimed to systematically summarize the characteristics of 95 TCM dominant diseases and provide a reference for the establishment of evaluation criteria for TCM dominant diseases. Methods . The diagnosis and treatment protocols of all the 95 TCM dominant diseases were screened. The data of disease classification, diseases' code of TCM, length of hospital stay, treatment protocols, and clinical pathways were reviewed and summarized. Results . The diseases of the genitourinary and nervous systems accounted for 14.74% and 12.73% of the TCM dominant diseases, respectively. The length of hospital stay for 55 (57.89%) diseases was no more than less than 14 days. Each disease had its specific Chinese herbal decoction pieces and Chinese patent drugs. Chinese medical injections were not widely used. TCM external treatments for these diseases are abundant, with hundreds optional. Conclusion . Some potentially promising TCM dominant diseases remain to be identified and deserve further research to establish the evaluation criteria of TCM dominant diseases.